The public perception and normative valuation of executive compensation: An international comparison - Andreas Kuhn (Institute for the Study of Labor (IZA), 2010)
This paper describes individuals' perceptions and normative valuations of executive compensation using comparable survey data for fifteen OECD member countries. An overwhelming majority of individuals (more than 90%) believes that top executives earn more than they actually deserve. However, there is also substantial variation in the actual and ethical levels of executive compensation, both within and across countries. The empirical analysis further shows that subjective estimates of executive pay are associated with objective measures of inequality and redistribution, and that individuals' perceptions and normative valuations of executive compensation are associated with their more general political preferences.
Keywords: D31; D63; J31; 330; executive compensation; subjective wage estimates; political preferences